2018
DOI: 10.1016/j.aquatox.2017.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Estrogenic and anti-androgenic effects of the herbicide tebuthiuron in male Nile tilapia (Oreochromis niloticus)

Abstract: Tebuthiuron is a phenylurea herbicide widely used in agriculture that can reach the aquatic environments, possibly posing negative effects to the aquatic biota. Phenylurea herbicides, such as diuron, are known to cause estrogenic and anti-androgenic effects in fish, but no such effects were yet reported for tebuthiuron exposure. Thus, the aim of this study was to evaluate if tebuthiuron, at environmentally relevant concentrations (100 and 200ng/L) and after 25days of exposure have estrogenic and/or anti-androg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 61 publications
(72 reference statements)
0
7
0
1
Order By: Relevance
“…Almeida et al [42] observed estrogenic and anti-androgenic effects with altered in spermatogenesis and in the size of the gonads on Oreochromis niloticus exposed to tebuthiuron in concentrations of approximately 1.5 times lower than the highest concentration detected in the searchers of this survey.…”
Section: Resultsmentioning
confidence: 54%
“…Almeida et al [42] observed estrogenic and anti-androgenic effects with altered in spermatogenesis and in the size of the gonads on Oreochromis niloticus exposed to tebuthiuron in concentrations of approximately 1.5 times lower than the highest concentration detected in the searchers of this survey.…”
Section: Resultsmentioning
confidence: 54%
“…The frequencies of points on different structures were calculated (no. points × 100/total points) using the same method applied by Alvarenga and França (); Criscuolo‐Urbinati, Kuradomi, Urbinati, and Batlouni (); De Almeida, Pereira, Batlouni, Boscolo, and Almeida (); Pereira, Boscolo, Moreira, and Batlouni ().…”
Section: Methodsmentioning
confidence: 99%
“…The results of the volume density evaluation were used to define the ovarian maturation stage, following traditional methodology applied for describing the reproductive cycle of tropical migratory (Borella, Chehade, Costa, & Batlouni, ; Rizzo & Bazolli, ) and other fish (Grier, Neidig, & Quagio‐Grassioto, ; Mañanós, Duncan, & Mylonas, ). To determine reproductive classes, we used the data obtained by volume density following methodology applied with some adjustments for the species under study (De Almeida et al, ; Kuradomi, Foresti, & Batlouni, ; Lira, Kuradomi, Souza, Hainfellner, & Batlouni, ; Pereira et al, ). Briefly, ovaries predominantly occupied by PV and lacking VI were considered "resting/immature"; ovaries presenting PV, CA and VI (volume density <10%) were considered "in maturation"; ovaries presenting VI (volume density >20%) and lacking POF were considered "mature"; ovaries with the presence of POF and VI were considered "spawned"; and ovaries that presented AT (>10%) were defined as "atretic.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fat samples were also collected from the fish and the following pesticides were quantified: DDT, DDE, DDD, endosulfan, dieldrin, endrin, and lindane. Environmentally relevant concentrations of herbicides have also been found to cause oestrogenic and anti-androgenic effects in tilapia species elsewhere, including Nile tilapias ( O. niloticus ) native to northern Africa ( De Almeida et al , 2018 ).…”
Section: Endocrine Disrupting Effects Observed In South African Watermentioning
confidence: 99%